Pengaruh Lingkungan Kerja, Pengalaman Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Pendidikan Kota Tanjungbalai - Sari, Dewi Mayang; Simanjuntak, Veronika; Apridah, Ruri; Siregar, Sri Juliani; Syah, Amirul; Isnaini, Dewi Budiarti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this study is to investigate how the work environment, work experience, and work discipline of Tanjungbalai City Education Service employees impact performance. The exploration strategy utilized was a study by dispersing polls to representatives of the Tanjungbalai City Instruction Office. The employees of the Education Department were chosen at random to be included in the research sample. An information examination was completed utilizing relapse procedures to evaluate the connection between free factors (workplace, work insight and work discipline) and the dependent variable (representative execution). The consequences of the examination show that the workplace decidedly affects the presentation of Tanjungbalai City Training Division representatives. Work experience likewise makes a positive commitment to further developing representative execution. Work discipline was likewise found to significantly affect representative execution. In general, these three free factors affect the presentation of Tanjungbalai City Schooling Office representatives. The consequences of this examination can add to the administration of the Training Division in further developing representative execution by focusing harder on and upgrading the workplace, giving decent work insight, and further developing representative work discipline. The ramifications of this examination can likewise be a reason for further developing HR strategies and practices in comparable organizations.